Optimalisasi Gizi Lansia melalui Pelayanan Gizi di Panti Bina Lansia Pos 7 Sentani - Elisabet Bre Boli; Koherista G. Liufeto; Oktliana Pasangka; Dwi Astuti; Benny Abraham Bungasalu (LPPM Akbid Harapan Ibu Pekalongan, 2026)
The aging process, accompanied by physical, psychological, and social decline, increases vulnerability to both non-communicable and infectious diseases among elderly. Improving elderly’ health can be achieved through nutritional status assessment and targeted nutritional interventions. Elderly residing at Panti Bina Lansia Pos 7 have not yet received adequate dietary intake, as identified through previous community service activities and field observations, which may increase the risk of malnutrition. This community-based activity aimed to assess the nutritional status of elderly and improve their dietary intake. Anthropometric measurements were conducted using a digital weighing scale, stadiometer, and knee-height caliper. Nutritional supplementation was provided in the form of pumpkin pudding and watermelon juice. The results indicated that the mean body weight and height of participants were 48.8 kg and 150.2 cm, respectively. All participants consumed the provided supplementary foods. This activity contributed to improving dietary intake and supporting the nutritional status of elderly. Regular implementation of similar nutrition-focused community interventions is recommended to promote and maintain healthy aging.